The Influence of Social Media Brand-Related Communication on Brand Equity and Consumer Response Towards Online Bootcamp Brands in Indonesia - Adhisakti, Gregorius; Hadiprawoto, Triana Rahajeng (Dinasti Publisher, 2024)
Education technology industry in Indonesia is experiencing rapid growth, marked by increased adoption and projected revenues, leading to the emergence of companies offering bootcamp services and using social media as a primary promotional tool. This study aims to examine the impact of social media brand-related communication, specifically Firm-Created Content (FCC) and User-Generated Content (UGC), on Brand Equity and consumer response in the online bootcamp market in Indonesia. Using a quantitative approach and online survey method, data were collected from 203 respondents and analyzed using Structural Equation Modeling (SEM). The study reveals that both FCC and UGC are effective tools for building brand equity and enhancing consumer response. Therefore, online bootcamps should focus on developing and implementing effective FCC and UGC strategies to achieve success in this competitive market